Analysis of outpatient service satisfaction in the pharmacy installation of Kendari City Hospital, Southeast Sulawesi Province in 2022 - Kartiwi, Wiwi; Oetari, R.A.; Saptarini, Opstaria (Institute of Computer Science (IOCS), 2024)
The quality of service in the hospital is very important to support the quality of the hospital in order to strive to create the best service and treatment for every patient. The purpose of this study was to determine the overall level of outpatient satisfaction with the quality of service and complaint handling at the pharmaceutical installation of Kendari City Hospital. In this study, it is descriptive with qualitative and quantitative approaches. Then the data obtained is processed using gap analysis, custumer satisfaction Index (CSI), and Importance Performance Analysis (IPA) to identify the strengths and weaknesses of the service and determine opportunities to develop strategic planning. The results of the gap analysis show that each dimension of the servqual is at a negative index, which means that the patient is not satisfied with the services provided, namely tangibles -0.24, reliability -0.17, responsiveness -0.22, assurance -0.16, empathy -0.54. The results of the CSI analysis of the servqual dimensions and overall complaint handling have not reached 100% (excellent) but have received a value of 91.75% (excellent). The results of the IPA analysis show that quadrant A is a priority in improvement, namely: the tangibles dimension, namely the availability of drugs and the responsiveness dimension, namely the waiting time for drugs.